If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -15 = 2x + -8 Reorder the terms: -15 + 16x = 2x + -8 Reorder the terms: -15 + 16x = -8 + 2x Solving -15 + 16x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + 16x + -2x = -8 + 2x + -2x Combine like terms: 16x + -2x = 14x -15 + 14x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + 14x = -8 + 0 -15 + 14x = -8 Add '15' to each side of the equation. -15 + 15 + 14x = -8 + 15 Combine like terms: -15 + 15 = 0 0 + 14x = -8 + 15 14x = -8 + 15 Combine like terms: -8 + 15 = 7 14x = 7 Divide each side by '14'. x = 0.5 Simplifying x = 0.5
| 5z-3=z+9 | | 2=s+18 | | x^2-9x+2=36 | | 9x-5=21+3 | | 2-9t=0 | | m-39=-11 | | 7r^2-4r+7=0 | | y=-3(3)+5 | | 40a^3+5b^3= | | -3y-15=45 | | 7x+3(x-2)=6(x+1)-3 | | 2(k+5)-3=k+18 | | Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 |